Clinical prognosis of surgical resection versus transarterial chemoembolization for single large hepatocellular carcinoma (≥5 cm): A propensity score matching analysis. Issue 3 (10th January 2023) - Hsieh, Pei‐Min; Hsiao, Pojen; Chen, Yaw‐Sen; Yeh, Jen‐Hao; Hung, Chao‐Ming; Lin, Hung‐Yu; Ma, Ching‐Hou; Tang, TaoQian; Huang, Yu Wei; Cheng, Pin‐Nan; Hsieh, Kun‐Chou; Hu, Kuang‐Chun; et al.
Abstract: Favorable prognostic factors and therapeutic strategies are important for patients with single large hepatocellular carcinoma (HCC). This retrospective study aimed to investigate the prognostic factors in patients with single large (≥5 cm) HCC with Child‐Pugh (CP) class A patients and to recommend therapeutic strategies. Overall, 298 HCC patients with single and large (≥5 cm) tumors with CP class A, but without distant metastasis and macrovascular invasion were included, and their clinicopathological data, overall survival (OS), and progression‐free survival (PFS) were recorded. OS and PFS was analyzed by the Kaplan–Meier method and Cox regression analysis. Propensity score matching (PSM) analysis was performed. The 298 HCC patients were 79.2% male and median age of 64 years. For the initial treatment, surgical resection (SR) and transarterial chemoembolization (TACE) was 50.8% and 49.2%, respectively. The OS and PFS were significantly higher in patients receiving SR than those receiving TACE before and after PSM. Furthermore, in multivariate analysis, cirrhosis (Hazard ratio [HR]: 2.04; 95% confidence interval [CI]: 1.35–3.03, p < 0.001, CP class A5/6 [HR: 4.01; 95% CI: 2.43–6.66, p < 0.001], and initial treatment [SR vs. TACE HR = 3.23; 95% CI: 2.13–5.01, p < 0.001]) remained significantly associated with mortality. Moreover, in multivariate analysis, CP class A5/6 (HR: 3.23; 95% CI: 1.89–5.88, p < 0.001), and initial treatment (Resection vs. TACE; HR = 4.17; 95% CI: 1.64–8.33, p = 0.039) remained significantly associated with recurrence. In conclusion, SR was associated with significantly higher OS and PFS rates than TACE before and after PSM for single large HCC patients.